How visual information constraints the approach of the wall for tumble-turn? - Seifert, L.; Puel, F.; Komar, J.; Guignard, B. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The aim of this case study was to investigate the role of the visual source of information to approach the wall in order to perform the tumble turn in swimming. The approach of the wall is represented by a T-line located at 2m from the edge of the swimming pool. To understand how this visual information is picked up by the swimmers to approach the wall, the T-line position was manipulated: normal T-line position (T), T-line 30cm backward (T30), and T-line 60cm backward (T60). One national swimmer had to swim 12 x 25m, corresponding to two trials at 70% and 90% of their maximal 25m swimming speed in three T-line positions. The swim speed was collected by aerial side camera. The speed at 3m to the wall, the distance between the head and the wall at the initiation of the rotation were computed from an underwater camera located at 3m from the wall. The stroke rate and the index of coordinationwere computed from three inertial measurement units located on the left wrist, right wrist and hip. The results highlighted that stroke rate further varied when the swimmers approached to the wall, accompanied by fluctuations of the index of coordination. These findings were more pronounced for the 90% pace and more marked for T60. In the meantime, head-wall distance and the speed at 3m to the wall further decreased for the 90% pace at T60 than for the other conditions of speed and T position.